Challenge in the Identification of Water Loss, Aromatic Sense, and Preference of Chili Paste During Ozone Water Controlled Handling. Issue 1 (1st May 2022) - Al-Baarri, A N; Mawarid, A A; Abduh, S B M; Legowo, A M; Rusmiadi, Z T S; Muflihani, S K; Fisabilla, S; Dewi, R K; Anggriyani, F S; Lestari, F P; Pangestika, W; Mulyana, H.; et al.
Abstract: Chili production received significant attention from Indonesian farmers due to the national income based on agricultural products. As happen in Indonesia, chili production depends on the season, resulting in the national stock and the price. The second-grade chili is easily available in the traditional market with low-medium quality but less shelf life quality. This research identified the treatment of chili using ozone after harvesting. Basic processing was used to produce chili paste. A10 kg of second-grade chili from a local farm was obtained. The chili without ozone was also used as control. The treatment for chili was washed in ozone through the method of ozone water. Chili paste was packaged in the aluminum packaging and heating. The chili paste was stored at room temperature for 12 days and the tests were conducted in every 6 days. This research had not shown a significant increase in water loss, but the aroma of chili had significant changes in the last day. Aromatic sense was obtained from consumer preferences upon the color of chili paste which indicated less changes in chili paste. In conclusion, chili paste with ozone treatment provided a remarkable positive effect on water loss, aromatic sense, and consumer preference.